1. a and b are the legs of a triangle and c is the hypotenuse

A(squared) + b(squared) = c(squared) means that the squared legs of a triangle equals the hypotenuse squared.

2. A(squared) + b(squared) = c(squared)

A=12cm B=5cm (12x12) + (5x5) = c(squared)

144+25=169

the square root of 169 equals the side length of c

c=13

3. A(squared) + B(squared) = c (squared)

A=8cm B=6cm (8x8) + (6x6) = c(squared)

64 + 36 = 100

the square root 100 equals the side length of c

c=10 this is a right triangle because the hypotenuse is longer then the legs

3.4 pages 104-105 #3-16

3. A) A(squared) + B(squared) = C(squared)

C(squared) = (12x12) + (16x16)

C(squared) = 144+256

C(squared) = 400

the square root of 400 equals the side length of c

C=20cm

B) A(squared) + B(squared) = C(squared)

R(squared) = (30x30) + (16x16)

R(squared) = 169 + 126

R(squared) = 295

the square root of 295 equals the side length of C

R = 17.17cm

4.A) A(squared) + B(squared) = C (squared)

Z(squared) = (7x7) + ( 6x6)

Z(squared) = 49 + 36

Z(squared) = 85

the square root of 85 equals the side length of C

Z=9.2

B) A(squared) + B(squared) = C(squared)

(8x8) + (11x11) = C(squared)

64 + 121 = 185

the square root of 185 equals the side length of c

C=13.6cm

5.A)6x6=36

8x8=64

B) 36+64=100

C) the square root of 100 is 10

## No comments:

## Post a Comment